2020
DOI: 10.31234/osf.io/qrjza
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Video game play is positively correlated with well-being

Abstract: People have never played more video games and many stakeholders are worried that this activity might be bad for players. So far, research has not had adequate data to test whether these worries are justified and if policymakers should act to regulate video game play time. We attempt to provide much-needed evidence with adequate data. Whereas previous research had to rely on self-reported play behaviour, we collaborated with two games companies, Electronic Arts and Nintendo of America, to obtain players’ actual… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 55 publications
(76 reference statements)
2
14
1
Order By: Relevance
“…In addition to the complexities in determining causal relations, the self-report nature of the current data presents unique problems. Although self-report measures of mental health and technology use have high face validity, they might be poor representations of the actual state of affairs (Shaw et al, 2020): In studies of this topic, self-report measures of technology use are consistently biased and are not highly correlated with objective use (Johannes et al, 2020;Parry et al, 2020;Scharkow, 2016). Additionally, true changes in technologies and their associations with health could be difficult to observe in between-persons data because adolescents, too, might change and e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the complexities in determining causal relations, the self-report nature of the current data presents unique problems. Although self-report measures of mental health and technology use have high face validity, they might be poor representations of the actual state of affairs (Shaw et al, 2020): In studies of this topic, self-report measures of technology use are consistently biased and are not highly correlated with objective use (Johannes et al, 2020;Parry et al, 2020;Scharkow, 2016). Additionally, true changes in technologies and their associations with health could be difficult to observe in between-persons data because adolescents, too, might change and e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that have adopted more systematic approaches to estimating associations between well-being and technology engagement have shown that the resulting relations depend on gender, arbitrary analytic choices, and the exact variables included in the analyses (Bjerre-Nielsen et al, 2020;Jensen et al, 2019;Kreski et al, 2020;Orben et al, 2019). In addition, most of this literature is limited by its use of self-reports of technology use, which are known to be biased and noisy indicators of true amounts of engagement, and lead to inaccurate estimated relations between health and well-being (Johannes et al, 2020;Parry et al, 2020;Scharkow, 2016;Shaw et al, 2020). Nevertheless, recent analyses and reviews have shown a trend whereby individuals who report greater technology engagement tend to also report higher levels of mental health problems, but the factors underlying these cross-sectional relationships still remain poorly understood (Appel et al, 2020).…”
Section: Understanding Digital Harmmentioning
confidence: 99%
“…Each feature of loot boxes here may moderate the effects of others, and thus evidence for effects of a given feature must be understood as limited to a particular context, and ideally reached after controlling for other features around it. Given this, natural experiments (e.g., Zendle, 2019) and industry collaborations (e.g., Johannes et al, 2020) will likely be crucial sources of data.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in our study, some teams were able to manage their well-being internally by engaging themselves purposefully in recreational communication and activities on a regular basis. These activities included, in many cases, playing online games together, which is insofar obvious because games are their shared passion, but worth mentioning as recent research has shown a positive relation between (social) gaming and well-being (Johannes et al, 2020). It can be concluded that future courses on remote work should explicitly educate students in coping with the psychosocial challenges of working remotely over physical distance.…”
Section: Discussionmentioning
confidence: 99%